BOUNDARY ELEMENT MODELLING OF ACOUSTIC FIELDS GENERATED DURING ULTRASONIC ANGIOPLASTY - D. Stepanenko; V. Minchenya (Наука и техника)
The article studies possibility of application of boundary element method (BEM) to modelling of acoustic fields generated during ultrasonic angioplasty. It is shown that modelling by means of BEM can be more efficient that traditionally used modelling by means of finite element method (FEM). Test problem of calculation of acoustic field created by ultrasonic waveguide in semi-infinite fluid medium is considered. The problem is solved by means of BEM and FEM and comparative analysis of results is provided. Modelling by means of BEM additionally involves application of mirror source method for avoidance of treatment of infinite fluid boundary.